Rekomendasi Pemilihan Mitra Kerja Proyek Dengan Menggunakan Metode Electre Pada Perusahaan Industri - Susliansyah, S; Kusnadi, Yahdi; Irfiani, Eni; Indriyani, Fintri (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Industrial companies, which are one of the players in the economy, are currently experiencing increasingly fast and rapid competition in industrial development. Industrial companies in selecting partners are still using the conventional way of recording partner data and assessing each partner, but some of these records are missing, making it difficult for the company to choose which one has a good performance. In addition, the company still applies subjective methods, namely based on the experience of being partners and being close to people who have power, in the end the company is unable to recommend which partners to accept or which are not accepted. The method that will be used to solve problems is by using the ELECTRE method, which has seven stages, namely Normalization of the Decision Matrix, Weighting the Normalized Matrix, Determining Concordance and Discordance Sets on the Index, Calculating Concordance and Discordance Matrices, Calculating Dominant Concordance and Discordance Matrices, Determine, Aggregate Dominance Matrix and Elimination of Less Favorable Alternatives. The results show that A2, A8 and A4 are the best alternatives from the other 12 alternatives. While the lowest alternatives are A1, A3, A5, A6, A7, A9, A10, A11 and A12.